PENGEMASAN PUREE CABE MERAH DENGAN BERBAGAI JENIS PLASTIK YANG DIKEMAS VAKUM - Dharia Renate (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2009)
This research was aimed to find the best type of plastic packaging to prolong the shelf life of chilli (Capsicum annuum L.) puree in the vacuum packaging system. The research was done in the laboratorium of Rekayasa dan Proses Pengolahan Hasil Pertanian Fakultas Pertanian Universitas Jambi. The types plastic use were thick polypropilen, thin polypropilen, and high density polyetilen. The storage time was 60 days. The samples were analyzed for their water content, vitamin C, total soluble solid, pH, capsaicin content and total microba every 15 days (0, 15, 30, 45, 60). The results show that the type of plastic packaging significantly affected the quality of the chilli puree stored for 60 days. The best treatment was found in chilli puree vacuumly packed in thick polypropylene and stored for 2 months. The puree has the characteristic of 79,10% water content, 36 mg/100 gr of vitamin C and pH of 4,14. Keywords: red chilli, vacuum packaging, polypropilene